2019
DOI: 10.4103/idoj.idoj_306_18
|View full text |Cite
|
Sign up to set email alerts
|

A survey of treatment practices in management of psoriasis patients among dermatologists of Kerala

Abstract: Introduction: The management of psoriasis is a daily challenge for dermatologists as most patients present with varied morphological presentations and exacerbations at every visit. This exerts a heightened responsibility on the dermatologists to tailor their treatments according to each patient. Aims: This study was conducted to assess the variation in treatment practices in the management of psoriasis patients among dermatologists of Kerala. Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Nazeer et al assessed the variation in management practices of psoriasis among dermatologists in Kerala, South India. 20 They found that most dermatologists rely on BSA, rather than PASI or PGA, due to time constraints. Furthermore, DLQI was not assessed by the majority of dermatologists.…”
Section: Discussionmentioning
confidence: 99%
“…Nazeer et al assessed the variation in management practices of psoriasis among dermatologists in Kerala, South India. 20 They found that most dermatologists rely on BSA, rather than PASI or PGA, due to time constraints. Furthermore, DLQI was not assessed by the majority of dermatologists.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the patients should be encouraged to contact dermatologists if they are experiencing any untoward effects. 27,28 It is important to encourage patients to live their life to full potential. Dermatologists should encourage their patients to join support groups or patient advocacy so that they could share their feelings with other patients.…”
mentioning
confidence: 99%
“…The herbs viz. Aloe vera, Curcumin longa, Silybummarianum and various oils like tree tea oil, black seed oil, coconut oil, etc., are reported to be used for psoriatic condition 7,8,9 . Cyclosporine is an immunosuppressant medication and natural product used in the treatment of psoriasis.…”
mentioning
confidence: 99%